Dampak Teknologi Informasi terhadap Masyarakat: Sebuah Kajian Mendalam - Soraya Albina (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Information technology (IT) has experienced rapid development over the past few decades, significantly impacting various aspects of society, including social, economic, cultural, and educational spheres. This article aims to examine the effects of IT on society, using a multidisciplinary approach to provide a comprehensive understanding of the positive and negative consequences of this technological advancement. Through in-depth analysis, the study reveals that IT enhances efficiency, broadens access to information, and opens new economic opportunities, but it also presents challenges such as the digital divide, changes in social interaction patterns, and negative impacts on local culture. The article suggests the need for public policies that can effectively manage the impacts of IT to ensure the well-being of society as a whole.